If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3m-5)+(-m+7)=0
We add all the numbers together, and all the variables
(3m-5)+(-1m+7)=0
We get rid of parentheses
3m-1m-5+7=0
We add all the numbers together, and all the variables
2m+2=0
We move all terms containing m to the left, all other terms to the right
2m=-2
m=-2/2
m=-1
| 3(4p+5)=6(p-2) | | -5(5x+1)=10 | | x2+3x4-2x=7 | | 6.3x+3=4.8x-6 | | 3x+13=8x+23 | | 10u=3+9u | | -4x+12x+20=124 | | (x+4)/x-2=0 | | 8y+7=16 | | (2x+5)+(6x+5)=90 | | 2(8m-7)=(3+4m) | | 11r-2r+15=24 | | 3800=(12.57x)/12 | | 3(-4x-6)=18 | | (x-4)/4+6/(x+1)=5/4 | | -2q=3-q | | X-y=-21 | | 7x+10=15;x=2 | | 5c+3=23 | | 7x24=3x92 | | -4x+7=11-4x+7=11 | | 1/2n-2n/16=3/8 | | 3800=(3.1415926(4)x)/12 | | 11=4z-21 | | W=3-4m | | 8r2+7r−1=0 | | i=(885)(0.02)(8) | | 3800=(π(4)x)/12 | | 2w+15w-21=47 | | -40=-4x-40=4x | | -2(x+3)+3=3(x+5)+4 | | (14x-15)+(x)-90=0 |